Effect of Oral Glucose on Pain Response in Infants during Invasive Procedures: A Review Article - Gogoi, Nirmali; Lalbiakzuali, Doris (Issues and Development in Health Research Vol. 3, 2021)
Infants experience pain similarly and probably more intensely than older children and adults. Pain management in young babies has been largely neglected in more clinical settings, despite subjecting them to painful procedures. Also, invasive procedures has done a lot during neonates and infancy period and it is to believed that the non-pharmacological methods as administration of oral glucose before and during procedures may relieve the infants pain and provide a safe way to analgesia. This review article will help us in assuring the effectiveness of oral glucose on pain response in infants during invasive procedures.